Social media pressures on cultural authenticity in traditional Igbo wedding - Uka Uka Nwagbara (Discover Global Society)
Abstract The rapid digitalisation in Nigeria has transformed the way cultural traditions are engaged with, particularly through social media platforms like X. Igbo traditional weddings, notably "Igba Nkwu" (wine-carrying ceremony), are increasingly influenced by online trends, blending traditional and modern elements. This study investigates how Nigerian youths use X to engage with Igbo wedding ceremonies, and explores whether the platform promotes cultural preservation or contributes to cultural commodification and simplification. The analysis is guided by Social Constructionism and Uses and Gratifications Theory. The study employed a qualitative research approach, gathering data from 15 respondents, including brides, grooms, wedding vendors, cultural participants, and social media influencers. The findings reveal a complex interplay between tradition and modernity, with X serving as a platform for cultural hybridisation. While many respondents valued the platform’s ability to showcase Igbo culture, others expressed concerns about the commercialisation of weddings, where aesthetics often overshadow cultural depth. The study contributes to knowledge by revealing how X mediates the hybridisation of Igbo wedding traditions, demonstrating its dual role as both a platform for cultural preservation and a driver of commercialisation, thereby expanding existing discussions on the digital reconfiguration of traditional practices in non-Western contexts. To balance modernity with tradition, digital literacy and mindful engagement with social media are recommended.